Recovering sucrose from mechanical harvesting of green sugar cane - Maldonado Cevallos, César Augusto (2017)
Sucrose is the final product of the sugar cane (Saccharum officinarum L.) agroindustrial process and is a key factor in the sugar mills activities planning. The result of its production can be affected by several factors inherent to the type of harvest, and it is common that losses are generated due to the permanence time of the cane in the field (TPCC) and the presence of Trash. The purpose of this investi- gation was to evaluate the losses of sucrose in 3 different types of harvest, and to establish which type of harvest allows the cane to stay in the field, using data from 27 weeks of harvest. In order to estimate the sucrose of the sugarcane crop, a statistical model was elaborated by means of a multiple linear regression analysis, based on the variables TPCC and Trash, the main sucrose loss factors, taking into account the three types of harvest of the sugarcane crop: manual burned, mechanics burned and green mechanics. It was verified that in the mechanical harvest of cane in green is the best system to recover sucrose, although the presence of Trash is high, it is less the record of hours of permanence of the cane in the field (TPCC), which prevents its deterioration by bacterial effects.